Midterm clinical outcome following Edwards SAPIEN or Medtronic Corevalve transcatheter aortic valve implantation (TAVI): Results of the Belgian TAVI registry. Issue 3 (11th May 2015) - Collas, Valérie M.; Dubois, Christophe; Legrand, Victor; Kefer, Joëlle; De Bruyne, Bernard; Dens, Jo; Rodrigus, Inez E.; Herijgers, Paul; Bosmans, Johan M.; for the Belgian TAVI Registry Participants
<x xml:space="preserve">Abstract</x> Objective To assess midterm (3 years) clinical outcomes of transcatheter aortic valve implantation (TAVI) in Belgium using the Edwards SAPIEN valve or the Medtronic CoreValve transcatheter heart valve (THV). Background Medium and long term follow‐up data of both THVs are still relatively scarce, although of great clinical relevance for a relatively new but rapidly expanding treatment modality. Therefore, reporting mid‐ and long term clinical outcome data, coming from large "real world" national registries, remains contributive. Methods Between December 2007 and March 2012, 861 "real world" patients who were not candidates for surgical aortic valve replacement as decided by the local heart teams, underwent TAVI at 23 sites. Eleven sites exclusively used SAPIEN THV (n = 460), while 12 exclusively used CoreValve THV (n = 401). Differences in clinical outcomes by valve system were assessed, according to access route and baseline EuroSCORE risk profile (<10%: low, 10–20%: intermediate and >20%: high risk). Results Overall cumulative survival at 3 years was 51% for SAPIEN vs. 60% for CoreValve (P = 0.021). In transfemorally treated patients, SAPIEN and CoreValve had similar survival at 3 years for each of the baseline EuroSCORE cohorts (low risk: 72% vs. 76%, P = 0.45; intermediate risk: 62% vs. 59%, P = 0.94; high risk: 48% vs. 53%, P = 0.65). Conclusion Cumulative midterm 3 year survival after transfemoral TAVI in "real world" patients refused for surgery with similar baseline EuroSCORE risk profile is not different between SAPIEN or CoreValve. © 2015 Wiley Periodicals, Inc.